A Survey of Farmers’ Perceptions on Maize and Sorghum Storage Duration and Level of Pest Infestations in the Case of Two Selected Districts of Jimma Zone, Ethiopia - Nezif Abamecha (International Journal of Food Science)
This survey study was conducted in two districts of the Jimma zone from April to July 2020 in the community of farmers who store maize and sorghum. While in Ethiopia, like in other east African countries, Maize and sorghum were an important postharvest chain for food security and income sources for small-scale rural farmers. Yet, there is a high postharvest loss of grains due to poor storage handling, storage practice, and pest infestations. And therefore, this survey study was aimed at assessing grain storage duration and level of pest infestations in selected districts of Jimma zone, Ethiopia. Two districts, Tiro Afeta and Sokoru, were selected based on the production potential of maize and sorghum grain crops. Then, three Kebeles were randomly taken from each district. Finally, two of the district’s 6 Kebeles with a total of 333 households storing maize and sorghum were interviewed, while limited farmers in Tiro Afeta and Sokoru districts store sorghum 4.9% and 60.7%, respectively, for more than one year, and the current finding indicates that as long storage time, there is a prospect to be mold infestation.